Rancang Bangun Mesin Penggiling Sambel Pecel dengan Penerapan Antropometri Guna Meningkatkan Efisiensi dan Kepuasan Pengguna (Studi Kasus: UMKM Warung Pecel dan Rujak 46) - Krishartanto, Riski; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The sambel pecel grinding machine is a machine used to smooth the ingredients of sambel pecel. The ingredients for making sambel pecel consist of fried peanuts, brown sugar, red chili, garlic, lime leaves, and other ingredients. All these ingredients will be ground to make sambel pecel. UMKM pecel and rujak coffee shop 58 in the process of grinding sambel pecel still requires services from other places, so that condition causes the production process to be less efficient. The purpose of this research is to make a sambel pecel grinding machine part of the transmission system.The results of the design of the resource and transmission parts of the sambel pecel grinding machine are: the resource used is an AC electric motor with a power of 0.268 Hp and a rotation speed of 2900 rpm, the transmission used is a pulley and a type A V-belt to drive the grinder, the diameter of the drive pulley used is 65 m, the driven pulley is 130 mm, the length of the V-belt circumference is 711 mm, number of belts required 1 piece, and uses a WPA 40 gearbox with a ratio of 1: 20.